2007
DOI: 10.1159/000120028
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Chemotherapy in Combination with COX-2 Inhibitors and PPAR-Gamma Agonists in Recurrent High-Grade Gliomas – A Phase II Study

Abstract: Objectives: Combined treatment approaches targeting tumor as well as other cells contributing to tumor progression may control chemorefractory malignancies. Methods: A phase II trial was initiated to analyze the activity of continuously administered pioglitazone and rofecoxib combined with low-dose chemotherapy (capecitabine or temozolomide) in patients with high-grade gliomas (glioblastoma or anaplastic glioma). Results: Fourteen patients were evaluable for response and toxicity. Major side effects were palmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…PPARγ agonists have therefore been proposed as novel anti-neoplastic agents for the treatment of glioma, although currently these drugs have not been evaluated in serum-free glioma cell cultures or direct-to-xenograft animal models (Ellis and Kurian, 2014). A Phase II clinical trial evaluating treatment with pioglitazone, a relatively specific PPARγ agonist, in combination with the chemotherapeutic temozolomide and the COX2 inhibitor rofecoxib, did not demonstrate improved prognosis, and individual patient responses did not correspond to protein expression levels of COX2 or PPARγ (Hau et al, 2007). More studies are needed to evaluate the biological and functional roles of PPARs in glioma.…”
Section: Peroxisome Proliferator-activator Receptors Are Central Regumentioning
confidence: 99%
“…PPARγ agonists have therefore been proposed as novel anti-neoplastic agents for the treatment of glioma, although currently these drugs have not been evaluated in serum-free glioma cell cultures or direct-to-xenograft animal models (Ellis and Kurian, 2014). A Phase II clinical trial evaluating treatment with pioglitazone, a relatively specific PPARγ agonist, in combination with the chemotherapeutic temozolomide and the COX2 inhibitor rofecoxib, did not demonstrate improved prognosis, and individual patient responses did not correspond to protein expression levels of COX2 or PPARγ (Hau et al, 2007). More studies are needed to evaluate the biological and functional roles of PPARs in glioma.…”
Section: Peroxisome Proliferator-activator Receptors Are Central Regumentioning
confidence: 99%
“…In two phase II studies, troglitazone had no effect in either patients with breast cancer or colorectal cancer 176, 177 . Some clinical trials examining the effect of PPARγ ligands combined with other therapeutics revealed no effect for some studies 178, 179 , but positive results for patients with thyroid carcinoma and glioma 180182 . It is also worth noting that a chromosomal translocation that fuses the paired box 8 gene ( PAX8 ) with the PPARG gene is found in some cases of thyroid cancer 183 .…”
Section: Ppars and Cancer Treatment And Preventionmentioning
confidence: 99%
“…Combination therapy of PPARγ agonists and other agents has been shown to be more effective than using either agent alone. 108,109 Moreover, some studies suggest a cross-talk between PPARγ and EGFR signalling pathways. 77 should be given to the ligand employed.…”
Section: Safety Issues and Pparγ Agonists In Clinical Developmentmentioning
confidence: 99%